Mycobacteria causing human cervical lymphadenitis in pastoral communities in the Karamoja region of Uganda - Oloya, J.; Opuda-Asibo, J.; Kazwala, R.; Demelash, A. B.; Skjerve, E.; Lund, A.; Johansen, T. B.; Djonne, B. (Epidemiology & Infection)
Mycobacteria from lymph node biopsies of patients with cervical lymphadenitis reporting for tuberculosis treatment in Matany and Moroto Hospitals in the transhumant areas of Karamoja, Uganda were isolated and characterized. The AccuProbe1 culture identiﬁcation kits for Mycobacterium tuberculosis complex (MTC), M. avium complex (MAC) and M. avium were used to identify the isolates. Spoligotyping, IS901 PCR and IS1311 and IS1245 restriction fragment length polymorphism (RFLP) were used to characterize the isolates. Of the 43 biopsies, ten M. avium, seven M. tuberculosis, three M. bovis, and two M. intracellulare were isolated. Two isolates could not be identiﬁed with AccuProbe1 and from 19 samples no mycobacteria could be isolated. Three isolates with the Beijing spoligotype were identiﬁed from the seven M. tuberculosis isolates. The spoligopatterns of the M. bovis isolates had previously been detected in cattle in Uganda. Isolation of members of the MAC group reﬂects the complex interaction between the transhumant communities, water sources and their cattle. None of the M. avium isolates harboured IS901, and all showed several bands on IS1311 and IS1245 RFLP, in accordance with M. avium subsp. hominissuis. Composite dendrograms of IS1311 and IS1245 RFLP showed that the isolates were similar and identical patterns were found. The isolation of M. bovis conﬁrms the human infection with zoonotic mycobacteria in areas where consumption of raw milk and meat is routine. Isolation of environmental mycobacteria also conﬁrms their increasing role in human disease and the occupational risk of infection in the transhumant ecosystem in the absence of safe drinking water and environmental contamination.
Keywords: Mycobacteria; Human cervical lymphadenitis; Pastoral communities; Karamoja region